Perspectives on Online Education: A Snapshot of State Regulatory Framework Development in Elementary and Secondary Online Education - Luke J. Stedrak; Amanda L. Rose (Educational Considerations, 2015)
With the advent and growth of elementary and secondary online education in the United States, teaching and learning has undergone radical change with heretofore unimagined alternatives to traditional brick-and-mortar classrooms.
Keywords: Perspectives on Online Education; Curriculum; State Statutory Review; frameworks; Online Education; elementary; secondary